UPAYA PENINGKATAN PENDAPATAN ASLI DESA (PAD) MELALUI METODE PARTISIPATIF PADA PEMERINTAH DESA DUAWUTUN KECAMATAN NAGAWUTUNG KABUPATEN LEMBATA - Hidayati, Maria Yosefiani; Asa, Andreas Mario; Welin, Elisabeth Date Masan; Kelen, Veronika Boleng; Kleden, Marianus (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Village Original Revenue (PAD) is essential for village independence and development. Duawutun Village, Nagawutung Sub-district, Lembata Regency, is still dependent on government transfers, and the potential funds for PAD have not been properly utilized. This activity aims to increase PAD by empowering local potential, such as agricultural land and clean water sources. The methods used were observation, interviews, and community participation. Results showed improved farm management and clean water distribution systems. This has a positive impact on health, agricultural productivity and additional sources of income. This integrated management is expected to increase PAD sustainably and it is recommended to strengthen village institutions and cross-sector collaboration.